The Effect of Implementing the Department of Science and Technology-Forest Products Research and Development Institute (DOST-FPRDI) Website Implementation on Public Service Delivery - Monina Cheska L. Castro; Chester Alexis Buama; Bayani A. Guia; Marie Ann S. Gonzales; Regina E. Gloria; Desiree L. Wagan (Journal of Social Entrepreneurship Theory and Practice, 2025)
The Department of Science and Technology-Forest Products Research and Development Institute (DOST-FPRDI) has implemented a website to modernize public service delivery and promote accessibility to forest product-related technologies. However, the impact of this transformation on user satisfaction and service efficiency remains underexplored. This study used a quantitative approach to investigate the effects of a website on public service delivery. Specifically, this study aimed to (1) analyze the demographic profiles and usage patterns of website users, (2) identify challenges encountered in terms of service quality, accessibility, and user satisfaction, and (3) evaluate user perceptions of the website's role in technology acceptance and public service delivery. Data were collected through an online survey designed by the researcher and validated by field experts. The analysis employed statistical tools, including mean, standard deviation, and Pearson's correlation coefficient (r), to evaluate the findings. The results revealed a predominantly female user base aged 25-44, with overall high satisfaction and positive usability and service quality feedback. While the challenges were minimal, older users and females reported slightly more issues than the other groups. The study concluded that enhancing key factors, such as perceived usefulness, ease of use, and behavioral intention, could further optimize user evaluations of the website. These findings informed the development of an action plan to improve website usability, accessibility and overall user experience, thereby strengthening public service delivery.